Is horizontal transmission of the Ostreid herpesvirus OsHV-1 in Crassostrea gigas affected by unselected or selected survival status in adults to juveniles? - Degremont, Lionel; Guyader, Tanguy; Tourbiez, Delphine; Pepin, Jean-francois (Aquaculture, 2013)
Massive mortality outbreaks, mostly affecting spat Crassostrea gigas, have been reported in France since 2008. Disease investigations revealed that most of the mortality events are related to the detection of the Ostreid herpesvirus 1 (OsHV-1 μVar). Meanwhile, selection to improve the survival in juvenile C. gigas has been successfully implemented in this context and selected oysters were found disease-resistant to OsHV-1 infection. This paper reports the first investigation of the horizontal transmission of the disease throughout cohabitation trials within batch and between batches using unselected and selected oysters for their higher survival. Two batches, unselected (AC) and selected (AR), were produced in February 2009 and deployed in the field in August 2009. Mortality associated with OsHV-1 detection occurred within the first two weeks of the deployment to reach 19% and 56% for the AR and AC batches, respectively. The remaining alive oysters were then brought into the laboratory in March 2010 for the cohabitation trials to assess the potential horizontal transmission of OsHV-1 within batch or between one of the batches and a third. The third batch (J) was produced using unselected oysters in August 2009 and it was always kept in the hatchery and the nursery to isolate it from the mortality risk factors. At the end of the cohabitation trials in July 2010, no mortality was found for the cohabitation trials between AR and J oysters as well as for the AR oysters and also for the J oysters grown alone in a tank. Conversely, high mortality was reported for the cohabitation trials using the J and AC batches as well as for the AC oysters alone. For the later, mortality occurred 3 days post-spawning while the AR oysters, which also spawned the same day, did not suffer of any abnormal mortality. Disease screening revealed that OsHV-1 was not detected for the J batch in March 2010, while 4 and 46% of the AR and AC oysters were found positive seven months post-mortality, indicating a difference in potential reservoir ...